Laser and brachytherapy in the palliation of adenocarcinoma of the oesophagus and cardia. Issue 5 (November 1996) - Spencer, G M; Thorpe, S M; Sargeant, I R; Blackman, G M; Solano, J; Tobias, J S; Bown, S G
Abstract : BACKGROUND: Palliation of malignant dysphagia is possible by a variety of methods although all have significant drawbacks. Laser therapy is an effective and safe treatment but has to be repeated at four to five weekly intervals to maintain palliation. A means of augmenting the benefits while reducing the need for repeat treatments would be highly beneficial to these patients. AIMS: To prospectively explore the safety and efficacy of intraluminal radiotherapy (brachytherapy) when used to augment laser recanalisation for malignant dysphagia. PATIENTS: Nineteen patients with dysphagia due to advanced adenocarcinoma of the oesophagus or cardia were recruited. METHODS: All patients received laser recanalisation until able to swallow a soft diet or better, before the application of a single dose of brachytherapy (10 Gy at 1 cm from the source). Patients were followed up and treated promptly by further endoscopic means in the event of their dysphagia worsening. RESULTS: Six patients (32%) required no further treatment until death at a median of 10 weeks (range 1-20 weeks). Further therapy was required at a median of 11 weeks (range 4-37 weeks) after brachytherapy for those 13 patients with recurrent dysphagia. Subsequent symptom control required endoscopic intervention at an average of once every nine weeks. There was no mortality associated with laser or brachytherapy. Median survival from initial treatment and including the one survivor was 36 weeks (range 5-132 weeks). CONCLUSIONS: Laser plus brachytherapy offers a safe and effective means of palliating malignant dysphagia due to adenocarcinoma, with a longer dysphagia free interval than historical controls treated with laser alone.